Revelation and Convergence : Flannery O'Connor and the Catholic Intellectual Tradition - Bosco, Mark; Little, Brent (Book collections on Project MUSE., 2017)
Did Flannery O'Connor really write the way she did because and--not in spite of--her Catholicism? Revelation & Convergence brings together professors of literature, theology, and history to help both critics and readers better understand O'Connor's religious imagination. The contributors focus on many of the Catholic thinkers central to O'Connor's creative development, especially those that O'Connor mentioned in the recently discovered and published A Prayer Journal (2013), or in her many letters to friends and admirers. Some, such as Leon Bloy or Baron von Hügel, remain relatively obscure to contemporary readers. Other figures, such as Augustine of Hippo or St. John of the Cross, are well-known, but their connection to O'Connor's stories has received little attention. Revelation & Convergence provides a much-needed hermeneutical lens that is often missing from contemporary criticism, representing O'Connor's ongoing conversation with her Catholic theological and literary heritage, and provide a glimpse into the rich Catholic texture of her life and work.